2014
DOI: 10.1176/appi.ps.201300062
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Suicidal Ideation Among Parolees

Abstract: Results indicated that parolees have more life stressors and that providing them with access to health care might lower suicidal ideation. Because parolees were more likely to rate their health as poor, providing access to medical care may improve their quality of life and their chance of successful return to the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Although prior research has yielded evidence of a relationship between incarceration and suicide among the general population (Binswanger et al, 2007(Binswanger et al, , 2011Fazel et al, 2008;Rosen et al, 2008;Yu et al, 2014), few researchers have studied the link between incarceration and suicide among transgender individuals. The current study addresses this gap in the literature by focusing on the possible role of correctional policies on attempted suicide among transgender individuals who have been incarcerated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although prior research has yielded evidence of a relationship between incarceration and suicide among the general population (Binswanger et al, 2007(Binswanger et al, , 2011Fazel et al, 2008;Rosen et al, 2008;Yu et al, 2014), few researchers have studied the link between incarceration and suicide among transgender individuals. The current study addresses this gap in the literature by focusing on the possible role of correctional policies on attempted suicide among transgender individuals who have been incarcerated.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have begun to focus on the relationship between incarceration and suicide (Binswanger, Blatchford, Lindsay, & Stern, 2011; Binswanger et al, 2007; Fazel, Cartwright, Norman-Mott, & Hawton, 2008; Rosen, Schoenbach, & Wohl, 2008; Yu, Sung, Mellow, & Shlosberg, 2014). While many of these studies focus on the overall population of previously incarcerated individuals, certain populations of inmates face unique circumstances in the correctional system that may negatively impact their well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional suicide risk factors including unemployment, no access to health care, mental health issues, and substance dependence were all identified as risk factors for suicide attempts among a community corrections population (McCullumsmith et al, 2013). A recent study on SI of parolees showed that access to health care may lower the chances of SI among parolees (Yu, Sung, Mellow, & Shlosberg, 2014). Being older, White, and having a medical condition also increased the risk of suicide (Clark et al, 2013).…”
Section: Si and Suicide Attemptsmentioning
confidence: 99%
“…Although suicide attempt rates among incarcerated persons are up to six times higher than those living in the community, 8 data on suicide attempt following community re-entry are essentially unknown. Whereas large national surveys, such as the National Survey on Drug Use and Health, have been used to estimate suicidal ideation in those recently released from prison, 9 suicide attempts cannot be confirmed. However, in 2008, the U.S. Department of Veterans Affairs (VA) mandated that health system facilities track attempted suicides at local and national levels through oversight of local suicide prevention coordinators, 10 providing the rare opportunity to reliably examine suicide attempts.…”
Section: Introductionmentioning
confidence: 99%